Missouri’s Taxation of Remote Sellers in a Post-Wayfair World - Charles L. Merriweather; John T.M. Whiteman (Washington University Journal of Law & Policy, 2019)
In this paper the authors consider the impact of the Wayfair decision on the state of Missouri. The authors – two members of the Missouri Department of Revenue – consider especially the unique implications Wayfair has to a state such as Missouri that is not a member of the SSUTA. It further surveys responses being developed by the state legislature.
Keywords: Tax; SALT; State and local taxes; Tax law; South Dakota v. Wayfair Inc. 138 S. Ct. 2080 (2018); Quill Corp. v. North Dakota 504 U.S. 298 (1992); Use tax; Sales tax; E-commerce; Dormant commerce clause; Interstate commerce; Nat’l Bellas Hess Inc. v. Dep’t of Revenue of Ill. 396 U.S. 753 (1967); Complete Auto Transit Inc. v. Brady; 430 U.S. 274 (1977); Direct Mktg. Ass’n v. Brohl 135 S. Ct. 1124 (2015); SSUTA; Missouri